Implementing Federal Health Reform in the States: Who Is Included and Excluded and What Are Their Characteristics?. (26th September 2014) - Fried, Brett; Pintor, Jessie Kemmick; Graven, Peter; Blewett, Lynn A.
<x xml:space="preserve">Abstract</x> Objective To estimate the characteristics and number of nonelderly adults eligible and ineligible for Affordable Care Act (ACA) expansions. Data Sources and Settings Two secondary data sources are used in this analysis: the 2008 Panel of the Survey of Income and Program Participation (SIPP) and the 2009 American Community Survey (ACS). Study Design We use multiple imputation to incorporate model‐based uncertainty into the prediction of immigration status into the ACS from the SIPP. Key variables include place of birth, year of entry to the U.S., and health insurance coverage. Data Collection/Extracting Methods No primary data are used in this study. Principle Findings We estimate that potentially 3.5 million nonelderly adults will be excluded from the ACA Medicaid Expansion and 2 million from the health insurance exchanges because of their immigration status. We also find significant differences in estimates of excluded nonelderly adults across states. Conclusions Over 15 percent of income‐eligible uninsured nonelderly adults will be potentially excluded from the ACA coverage expansions due to their immigration status. Policy makers must be careful to exclude ineligible nonelderly adults before estimating the impact of the ACA on coverage rates.